Calcium-stimulated adenylyl cyclase subtype 1 is required for presynaptic long-term potentiation in the insular cortex of adult mice. (April 2019) - Miao, Hui-Hui; Li, Xu-Hui; Chen, Qi-Yu; Zhuo, Min
Recent studies indicate that presynaptic long-term potentiation in the anterior cingulate cortex may contribute to chronic pain-related anxiety. In addition to the anterior cingulate cortex, the insular cortex has also been indicated in chronic pain and its related emotional disorders. In the present study, we used a 64-channel multielectrode dish (MED64) system to record pre-long-term potentiation in the insular cortex. We showed that low-frequency stimulation paired with a GluK1-containing kainate receptor agonist induced N-methyl-D-aspartic acid receptor-independent pre-long-term potentiation in the insular cortex of wild-type mice. This form of pre-long-term potentiation was blocked in the insular cortex of adenylyl cyclase subtype 1 (AC1) knockout mice. Furthermore, a selective AC1 inhibitor NB001 blocked pre-long-term potentiation in the insular cortex with a dose-dependent manner. Taken together, our results suggest that AC1 contributes to pre-long-term potentiation in the insular cortex of adult mice and NB001 may produce anxiolytic effects by inhibiting pre-long-term potentiation in the anterior cingulate cortex and insular cortex.